2020
DOI: 10.1007/s12298-020-00788-0
|View full text |Cite
|
Sign up to set email alerts
|

Stevia rebaudiana Bertoni responses to salt stress and chitosan elicitor

Abstract: This study examined the effect of chitosan elicitor with four different concentrations (0, 0.2, 0.4 and 0.6 g/l) on physiological and biochemical properties of stevia under four levels of salinity stress (0, 50, 100, 150 mM level of NaCl). Salt stress caused reduction of chlorophyll a (Chl a), chlorophyll b (Chl b), total chlorophyll, carotenoid and total protein content. The increment of malondialdehyde (MDA) content was not significant in all NaCl levels, while the CAT and POX activities were increased as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 42 publications
3
26
0
Order By: Relevance
“…Several studies have found that salinity treatments reduce chlorophyll concentrations in stevia (Janah et al 2021), pepper (Taffouo et al 2017, bean (Alzahrani et al 2019), and peppermint (Fathi et al 2020), which probably happens due to the decreasing of Mg 2+ uptake, an essential mineral element for chlorophyll biosynthesis (Hashem et al 2014). Similar results were found by Gerami et al (2020) in stevia plants subjected to salt stress. However, the use of AMF has proven to have a beneficial effect on chlorophyll contents in this study..…”
Section: Discussionsupporting
confidence: 88%
“…Several studies have found that salinity treatments reduce chlorophyll concentrations in stevia (Janah et al 2021), pepper (Taffouo et al 2017, bean (Alzahrani et al 2019), and peppermint (Fathi et al 2020), which probably happens due to the decreasing of Mg 2+ uptake, an essential mineral element for chlorophyll biosynthesis (Hashem et al 2014). Similar results were found by Gerami et al (2020) in stevia plants subjected to salt stress. However, the use of AMF has proven to have a beneficial effect on chlorophyll contents in this study..…”
Section: Discussionsupporting
confidence: 88%
“…Oxidative stress is viewed as one of the most significant damaging factors in plant cells exposed to salt stress [ 17 , 18 ]. Plants grown in fields with high levels of salinity are affected by osmotic stress, and therefore, they encounter a great deal of negative effects at the morphological, physiological and biochemical levels [ 19 ]. It is difficult to detach systemic from cellular salinity tolerance mechanisms because of the structural complexity of the entire plant [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the previous study, the application of chitosan 0.4 g/L reportedly did not have a significant effect on sunflower (Helianthus annuus L.) [41] and sage (Salvia officinalis L.) [44]. However, the application of chitosan 0.4 g/L and 0.6 g/L can increase the growth parameter in basil (Ocimum basilicum) [45] and stevia (Stevia rebaudiana Bertoni) [46] significantly. That study shows that the application of chitosan 0.4 g/L and 0.6 g/L still has a significant effect on plant growth.…”
Section: Leaves Numbermentioning
confidence: 95%